(untitled) (The Review of Diabetic Studies, 2025)
Background: Overcrowding in hospital emergency units (HEU) occurs when demand exceeds the capacity to provide timely care, impacting patient outcomes and the overall management of the hospital and health network. This phenomenon is particularly concerning for patients with time-sensitive conditions. Methods: The study analyzes freely available data from the Department of Health Statistics and Information (DEIS) within the hospital emergency care model considering three components: access to the emergency room, emergency care process, and patient discharge. Circular processes, such as registration without available appointments and hospitalization without access to a bed, are identified as factors contributing to overcrowding. Results: The analysis reveals that the demand for emergency care is higher in primary care than in hospital care, with a significant increase in primary care demand from 2015 to 2023. The study also highlights the importance of categorizing emergency demand using the Emergency Severity Index (ESI), which ensures rapid clinical assessment and appropriate referral flows. Additionally, the study identifies the waiting time for hospital beds as a critical factor in overcrowding, with a significant percentage of patients waiting more than 12 hours. Conclusions: The study identifies critical nodes for overcrowding in the three components of the model. Strengthening primary health care and improving patient flow within emergency units are essential strategies to mitigate overcrowding. The study also emphasizes the need for comprehensive data on care times and hospital bed access to better understand and address overcrowding.